Agenda-Setting Theory in Megathrust Disaster Communication: A Content Analysis of Coverage in Kompas.com - Nunik Hariyani; Alfiana Yuniar Rahmawati; Azizah Choirunisa Azzahra (Mediakita, 2026)
This study analyzes how online media frames disaster issues through an agenda-setting theory approach, with a particular focus on identifying agenda elements, strengths, and weaknesses in messages related to the megathrust threat in Indonesia. Using qualitative content analysis, this study examined 24 articles published on the Kompas.com news portal between August 12 and 30, 2024. The findings show that Kompas.com consistently prioritized the megathrust issue, emphasizing threats in specific regions, such as the Sunda Strait and southern Java. The outlet successfully constructed a preparedness narrative by highlighting concrete mitigation measures, including the use of disaster preparedness bags and early warning systems. However, the analysis reveals weaknesses in the use of complex technical language and a tendency toward sensational framing that risks triggering excessive public anxiety without adequate mitigation counterbalance. Coverage was dominated by institutional actors (BMKG and BNPB), with active, independent community participation underemphasized. Theoretically, this research reinforces the agenda-setting mechanism, demonstrating that online media strongly tend to frame disaster issues through educational and preparedness narratives. In practice, it recommends that media balance urgency reporting with accessible, practical solutions to minimize negative psychological impacts on the public.